DEVELOPMENT OF THE COMPETENCE OF A TEACHER OF A VOCATIONAL EDUCATION INSTITUTION IN THE USE OF DIGITAL TECHNOLOGIES IN THE TRAINING OF FUTURE SKILLED WORKERS IN THE MECHANICAL ENGINEERING (Innovative professional education, 2024)
The development of digital competences of teachers of vocational education and training in the context of training skilled workers for the engineering industry is considered. The importance of integrating digital technologies into the educational process to ensure effective training of vocational education students to the requirements of modern engineering production is emphasized. It is noted that the continuous professional development of teachers and the introduction of the latest technologies are key tosuccessful learning.
Keywords: vocational education, digital technologies, VET, digital skills, digital competence, teachers of VET institutions